MAIN DIRECTIONS OF MODERN DEVELOPMENT OF STEEL CONSTRUCTIONS FOR BUILDINGS AND STRUCTURES (Collection of scientific works «Modern structures of metal and wood», 2021)
The development of technologies for the manufacture and design of steel structures, together with the development of computer technologies, makes it possible to increase productivity in the building industry.  The analysis and generalization of such factors made it possible to identify the main trends and directions of the creation and improvement of metal structures, taking into account the automation of their manufacturing processes and the use of BIM technologies. The highlighted tendencies make it possible to show both new directions for the development of scientific research and directions for the development of practical methodologies for determining the regularities of the stress-strain state of structural systems using steel. Among the main trends, the following are highlighted: digitalization of the metal construction industry; automation and robotization of the manufacturing and assembling processes;  science  intensity  of  design  and  production  processes;  greening  production,  evaluating design  solutions  from  the  standpoint  of  environmental  safety;  complex  optimization  of  design solutions.  The  authors  highlight  the  next  important  tasks  and  prospects  for  the  development  of  the creation of effective metal structures: the creation and use of high-strength steels C960 and more, the improvement of automated and robotic welding processes for ultra-high-strength steels with various metal thicknesses; development and improvement of the theory of calculation of thin-walled and composite  structures,  determination  of  the  actual  resource  of  metal  structures  after  long-term operation; introduction into the practice of creating new structures of rational and optimal design approaches  with  the  requirements  of  long-term  operation  and  life  cycle,  including  progressive collapse, reduction in the cost of fire and anti-corrosion covers for steel structures; improvement of building  codes  and  rules  for  the  design  of  metal  structures;  implementation  of  leading  foreign standards and experience; training of modern professional engineers and technicians; development of experimental and theoretical studies of full-scale samples of structures on the basis of creating high-precision information models of structural systems.